The interbank network across the global financial crisis: Evidence from Italy - Affinito, Massimiliano; Franco Pozzolo, Alberto (Journal of Banking & Finance, 2017)
This study examines the effects of the global financial crisis (GFC) on interbank market connectivity using network analysis. More specifically, using data on Italian banks’ bilateral interbank positions between 1998 and 2013, we analyze the impact of the following events on each bank's network centrality: the liquidity crisis in August 2007, the collapse of Lehman Brothers in September 2008, Eurosystem's long term refinancing operations (LTROs) between 2009 and 2012, the sovereign debt crisis in July 2011, and the announcement of Outright Monetary Transactions (OMT) in 2012. The results show that the 2007 liquidity crisis and especially the collapse of Lehman Brothers are associated with a marked reduction of the relative interconnectedness of the Italian banking sector (i.e., a shift in the distribution of banks’ centrality to the left, away from the most connected bank). In the following years, the system progressively recovered its initial patterns of integration among banks, which coincided with the main Eurosystem's monetary policy interventions. However, the average outcome conceals different results across banks, depending on their characteristics and initial positions within the system.